Controlled Release of Naproxen Sodium from Eudragit RS 100 Transdermal Film - Khatun, Masuda; Islam, SM Ashraful; Akter, Parvin; Quadir, Mohiuddin Abdul; Reza, Md. Selim (Dhaka University Journal of Pharmaceutical Sciences, 2007)
Polymeric films of Eudragit RS 100 were prepared by solvent casting method to explore the possibilities of using this polymer in transdermal therapeutic system (TTS). Naproxen was used as a model drug and incorporated in two different percent loading (8.3 % w/w and 20.8 % w/w of films). Effects of two plasticizers ( PEG 1500 and PEG 4000) and two release modifiers ( PVA and HPMC 15cps) on in vitro drug release from naproxen loaded eudragit RS films were assessed. Drug release was found to be a function of drug load, PEG molecular weight and physico-chemical property of the release modifiers incorporated. At low drug load, highest amount of drug was released from flims containing PEG 1500 (more than 95%). However, a burst release was evident in case of all the experimental batches except that loaded with HPMC 15 cps. With this formulation, more than 75 % of active principle was released after 8 hours while only 12 % of naproxen was liberated in the first hour of dissolution. Increasing drug load, increased the rate and extent of drug release from eudragit RS films; however this effect was minimized when PEG 4000 was used as release modifier. For PEG 1500 loaded films, drug release was decreased with increasing drug concentration in the TTS. Inclusion of PEG in eudragit RS films caused the drug to be released by diffusion (Fickian) kinetics whereas PVA and HPMC containing formulations released drug by diffusion mechanism coupled with erosion. Key words: Naproxen sodium, Eudragit RS 100, Controlled release.Dhaka Univ. J. Pharm. Sci. Vol.3(1-2) 2004The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website